Analisis Performa Website AyoMulai Menggunakan GTMetrix dan Page Speed Insights - Heidi Angela Tengriano; Arfan Yunus; Sudirman (STMIK KHARISMA Makassar, 2022)
AyoMulai is a crowdfunding platform for creative, this platform was created by the Four Clover founder team which can be accessed via the link https://ayomulai.id/. This research aims to analyze the performance of the AyoMulai website by using 2 help tools, namely GTMetrix and Page Speed Insights using a non-participan observation method where researchers only make observations on the AyoMulai website. Based on performance measurements on GTMetrix got a score of 77% and Page Speed insights with a score of 90, as for the results of 6 metrics, namely first contentful paint on GTMetrix (1.7 s) and Page Speed Insights (1.5 s), GTMetrix speed index (2.3 s) and Page Speed Insights (1.5 s), time to interactive GTMetrix (1.7 s) and Page Speed Insights (1.5 s), total blocking time GTMetrix (0 ms) and Page Speed Insights (0 ms), cumulative layout shift GTMetrix (0,02) and Page Speed Insights (0.034), and largest contentful paint GTMetrix (2.4 s) and Page Speed Insights (1.5 s). So it can be said that the performance of the AyoMulai website is quite good, and also in the use of these 2 tools have results that are not too much different which can be seen in 6 elements, namely first contentful paint, speed index, time to interactive, total blocking time, cumulative layout shift, and largest contentful paint which has a slight difference in numbers.